Biomass Production and its Accumulation in Coleus forskohlii Briq.: Impact of Spacing and Time of Harvest - Mastiholi, Anand Basavanni; Chavan, Mukesh Loknaath; -, Prabhuling Gurappa (JOURNAL OF ROOT CROPS, 2015)
A field experiment was carried out at Kittur Rani Channamma College of Horticulture, Arabhavi, Karnataka, for two years to study the influence of spacing and time of harvest on biomass production and its accumulation in Coleus forskohlii. Pooled analysis of yield data indicated that significantly higher total biomass (TBP) was produced when planted at a spacing of 60 cm x 20 cm (10.08 t ha-1) followed by 75 cm x 20 cm (9.92 t ha-1). There was increase in tuber biomass production with decrease in plant to plant spacing (1.04 t ha-1 at 60 cm x 30 cm and 1.57 t ha-1 at 60 cm x 20 cm). Shoot biomass accumulation was higher at 75 cm x 20 cm and 60 cm x 20 cm. Increase in biomass accumulation in tubers was not significant beyond 160 days after planting (DAP) (1.39 and 1.45 t ha-1 at 160 and 180 DAP, respectively). The total biomass production and its accumulation in the above ground portion and tubers were significantly higher in the treatment combinations, 60 cm x 20 cm at 180 DAP (11.15, 9.38 and 1.77 t ha-1, respectively) and also at 160 DAP (9.45, 7.72 and 1.73 t ha-1, respectively). Harvest index (HI) was found higher at closer spacing of 60 cm x 20 cm (0.121) and at 160 DAP (0.135). Interaction effects of spacing and time of harvest indicated that coleus cultivar K-8 may be planted at a spacing of 60 cm x 20 cm and harvested at 160 DAP to get higher tuber yield and harvest index.